2001
DOI: 10.1038/35065004
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin I functions as a calcium regulator of release probability

Abstract: In all synapses, Ca2+ triggers neurotransmitter release to initiate signal transmission. Ca2+ presumably acts by activating synaptic Ca2+ sensors, but the nature of these sensors--which are the gatekeepers to neurotransmission--remains unclear. One of the candidate Ca2+ sensors in release is the synaptic Ca2+-binding protein synaptotagmin I. Here we have studied a point mutation in synaptotagmin I that causes a twofold decrease in overall Ca2+ affinity without inducing structural or conformational changes. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
846
4
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 895 publications
(900 citation statements)
references
References 48 publications
41
846
4
9
Order By: Relevance
“…Third, the short linker between the two C2 domains would limit the orientations that the C2A domain can adopt, enhancing the rapid response to the calcium signal. In this orientation, C2A may respond to calcium entry either through binding electrostatically to the phospholipid membrane (Fernandez-Chacon et al, 2001) or, as has also been suggested, through the inducible, calcium-dependent, binding to SNAREs (Zhang et al, 2002;Bai et al, 2004). This inducible SYT/SNARE interaction exhibits properties very different from those characteristic of the constitutive association.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Third, the short linker between the two C2 domains would limit the orientations that the C2A domain can adopt, enhancing the rapid response to the calcium signal. In this orientation, C2A may respond to calcium entry either through binding electrostatically to the phospholipid membrane (Fernandez-Chacon et al, 2001) or, as has also been suggested, through the inducible, calcium-dependent, binding to SNAREs (Zhang et al, 2002;Bai et al, 2004). This inducible SYT/SNARE interaction exhibits properties very different from those characteristic of the constitutive association.…”
Section: Discussionmentioning
confidence: 94%
“…Genetic knockouts of SYT1 result in dramatic suppression of evoked release in several model organisms (Bellen, 1999;Sudhof and Scheller, 2001). Of the two C2 domains, mutagenesis of C2B has a more severe effect on the SYT-controlled fast synchronous release (Fernandez-Chacon et al, 2001;Mackler et al, 2002;Robinson et al, 2002). In Drosophila melanogaster, a single mutation of tyrosine to asparagine in the C2B domain severely disrupts calcium-triggered exocytosis (Yoshihara and Littleton, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not surprising that many of the proteins involved in the regulation of neurotransmitter release have also been identified in the pancreatic B-cell and demonstrated to participate in insulin secretion (Lang 1999 Söllner et al 1993), by tethering the granules to the plasma membrane (Sutton et al 1998). Synaptotagmin is the most likely candidate for the Ca 2π -sensor of the exocytotic machinery (Fernandez-Chacon et al 2001), and essential for Ca 2π -dependent neurotransmission (Littleton et al 1993) and exocytosis of insulin-containing granules (Lang et al 1997). It is a protein of 65 kDa that spans the vesicle membrane once and contains a large cytoplasmic domain with two Ca 2π -binding C2 domains (protein kinase C-homology domains), C2A and C2B (Sutton et al 1995).…”
Section: The Exocytotic Machinerymentioning
confidence: 99%
“…After the arrival of an action potential at an excitatory synapse, neurotransmitter release displays two components: 160 a fast and synchronous component triggered by the Ca 2 þ -sensor synaptotagmin 1 161,162 and a slow, asynchronous component that is also Ca 2 þ -dependent but not well understood from the molecular point of view. Calakos et al found that neurons from RIM1-alpha KO mice have an B50% reduction in the asynchronous component of release, which implies RIM1-alpha in a postpriming step related to Ca 2 þ -triggered vesicle fusion.…”
Section: Rim1-alphamentioning
confidence: 99%
“…162,122,174 Synaptotagmin 1 R233Q knockin mice bear a punctual mutation in the C2A domain of synaptotagmin 1, which impairs the Ca 2 þ -dependent phospholipid binding to the C2A domain and translates into an B50% decreased of Pr and increased short-term synaptic plasticity in cultured hippocampal neurons. 162 In contrast to the learning deficits in RIM1-alpha KO mice, the synaptotagmin R233Q knockin did not have any alterations in learning and memory. Interestingly, those results would indicate that a generalized decrease in Pr does not translate into a learning deficit.…”
Section: Rim1-alpha Is Critical For Learning and Memorymentioning
confidence: 99%